1992
DOI: 10.1037/0022-006x.60.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic empathy and recovery from depression in cognitive-behavioral therapy: A structural equation model.

Abstract: This study demonstrated that therapeutic empathy has a moderate-to-large causal effect on recovery from depression in a group of 185 patients treated with cognitive-behavioral therapy (CBT). The authors simultaneously estimated the reciprocal effect of depression severity on therapeutic empathy and found that this effect was quite small. In addition, homework compliance had a separate effect on clinical recovery, over and above the effect of therapeutic empathy. The patients of novice therapists improved signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
179
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(193 citation statements)
references
References 17 publications
(42 reference statements)
11
179
1
2
Order By: Relevance
“…However, the role of the use of homework and its compliance in the effectiveness of the treatment has been discussed between the researchers in the field. Beyond any position, the meta-analysis carried out by Kazantzis, Deane & Ronan (2000) showed that the depressed clients who completed most frequently the tasks assigned obtained greater improvements and this is congruent with the findings of Burns & Nolen-Hoeksema (1992) with a depressed sample. Nevertheless, although some studies using experimental methodology did not find the same results (see for example: Neimeyer & Feixas, 1990), the researchers suggested that the differences between the 'instructed' and the 'non-instructed' groups are visible in the maintenance, as the groups which received instructions showed that the improvement remained during the follow-up.…”
Section: The Role Of Instructions In Therapeutic Effectivenesssupporting
confidence: 65%
“…However, the role of the use of homework and its compliance in the effectiveness of the treatment has been discussed between the researchers in the field. Beyond any position, the meta-analysis carried out by Kazantzis, Deane & Ronan (2000) showed that the depressed clients who completed most frequently the tasks assigned obtained greater improvements and this is congruent with the findings of Burns & Nolen-Hoeksema (1992) with a depressed sample. Nevertheless, although some studies using experimental methodology did not find the same results (see for example: Neimeyer & Feixas, 1990), the researchers suggested that the differences between the 'instructed' and the 'non-instructed' groups are visible in the maintenance, as the groups which received instructions showed that the improvement remained during the follow-up.…”
Section: The Role Of Instructions In Therapeutic Effectivenesssupporting
confidence: 65%
“…Homework compliance was significantly higher among clients assigned to behavioral skills training rather than problem-solving training , but what may be of greater importance than program orientation is how homework is introduced to clients. Positive associations were found between homework compliance and therapists' empathy (Burns & Nolen-Hoeksema, 1992) and the use of motivational interviewing , which requires therapists' empathy and compassion (Catley et al, 2006;. Therefore, while greater examination of the treatment factors associated with homework compliance is required, there is an indication that therapist characteristics influencing motivation may be of greater relevance to homework compliance than program factors, and requires further research.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A notable gap in the homework research is the lack of focus on associated therapist characteristics and treatment factors, which were investigated in only three studies (Burns & Nolen-Hoeksema, 1992;. Homework compliance was significantly higher among clients assigned to behavioral skills training rather than problem-solving training , but what may be of greater importance than program orientation is how homework is introduced to clients.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There is considerable evidence that therapist effects are reduced in controlled clinical trials relative to naturalistic studies of clinical practice , presumably in part as a result of the greater training and supervision provided, as well as initial selection of talented therapists. This is not to say that all types of therapies require trained and experienced practitioners to produce maximum effect, but there is evidence that this is true for at least some types of interventions and for some populations (e.g., Burns & Nolen-Hoeksema, 1992 ;Lyons & Woods, 1991 ;Weisz, Weiss, Han, Granger, & Morton, 1995 ).…”
Section: Therapist Training and Monitoringmentioning
confidence: 99%